Seismic hazard assessment in Eastern and Southern Africa - G. Turyomurugyendo; D. K. Lombe; K. Atakan; F. Kebede; L. S. Chapola; D. J. Hlatywayo; V. Midzi; F. A. Tugume (Annals of Geophysics, 1999)
Seismic hazard assessment for the Eastern and Southern Africa region was done using the probabilistic approach. Seismic hazard maps for 10% exceedance in 50 years, 10% exceedance in 100 years, as well as for 50 and 100 years return periods were prepared using the FRISK88M software. The area involved covers a wide region bounded by latitudes 40°S-25°N and longitudes 10°E and 55°E. Input parameters for the computations were obtained using the recent earthquake catalogue compiled by Turyomurugyendo. The catalogue which covers the time period 627-1994, contains earthquakes within the area bounded by 40°S-25°N and 10°E-55°E, with homogeneous magnitudes (M S ). Since a Poisson model of earthquake occurrence is assumed, dependent events were cleaned from the catalogue. Attenuation relations for the Eastern and Southern Africa region based on the strong motion data are virtually non-existent. However, attempts have been made recently by Jonathan and Twesigomwe to establish an average attenuation relation for the region. These relations were used in the computations. Possible uncertainties in the attenuation relations were accounted for using the logic-tree formalism. The results are presented in seismic hazard maps in terms of Peak Ground Acceleration (PGA) for the mean and the 85th percentile. The distribution of PGA values indicate relatively high hazard along the East African rift system. In the northern segments of the rift system, they exceed 250 gals for 10% probability of exceedence in 50 years.